On differentiability of open mappings - Bondar, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
The well-known Men’shov and Gehring-Lehto theorems on the differentiability of topological mappings of plane domains are generalized to the case of continuous open mappings of many-dimensional domains.